Rice Bran Oil Decreases Total and LDL Cholesterol in Humans: A Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials - Jolfaie, N. R.; Rouhani, M. H.; Surkan, P. J.; Siassi, F.; Azadbakht, L. (Hormone and Metabolic Research, 2016)
Cardiovascular disease (CVD) has become a concerning health problem because of its increasing prevalence. Vegetable oils such as rice bran oil may improve blood lipids, risk factors for CVD. We performed a systematic review and meta-analysis to identify and quantify the effects of rice bran oil on lipid profiles in humans. Literature databases (Pubmed, Scopus, Science Direct, Proquest, Ovid, and Google Scholar) were systematically searched until the end of November 2015, with no restrictions regarding study design, time, or language. The variables extracted for the meta-analysis included low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), total cholesterol (TC), triacylglycerol (TAG), VLDL-C, apoA, apoB, Lp(a), TC/HDL-C, and LDL-C/HDL-C. From 415 identified articles, 11 randomized controlled trials met the eligibility criteria and were included in our review. Rice bran oil consumption resulted in a significant decrease in concentrations of LDL-C (–6.91 mg/dl, 95% CI, –10.24 to –3.57; p<0.001) and TC (–12.65 mg/dl; 95% CI, –18.04 to –7.27; p<0.001). The increase in HDL-C levels were considerable only in men (6.65 mg/dl; 95% CI, 2.38–10.92; p=0.002). Results of our meta-analysis provided no evidence of a significant effekt of rice bran oil on other lipid profile components. In conclusion, consumption of rice bran oil can reduce LDL-C and TC concentrations, which may lead to prevention and control of CVD. It also has favorable effects on HDL-C concentrations in men. However, changes related to other lipid profile components are not considerable.
Keywords: rice bran oil; low density lipoprotein cholesterol; high density lipoprotein cholesterol; total cholesterol; triacylglycerol